Low‐dose 2.5 MV cone‐beam computed tomography with thick CsI flat‐panel imager. (8th July 2016) - Tang, Grace; Moussot, Christopher; Morf, Daniel; Seppi, Edward; Amols, Howard
Abstract : Most of the treatment units, both new and old models, are equipped with a megavoltage portal imager but its use for volumetric imaging is limited. This is mainly due to the poor image quality produced by the high‐energy treatment beam ( > 6 MV). A linac at our center is equipped with a prototype 2.5 MV imaging beam. This study evaluates the feasibility of low‐dose megavoltage cone‐beam imaging with the 2.5 MV beam and a thick cesium iodide detector, which is a high‐efficiency imager. Basic imaging properties such as spatial resolution and modulation transfer function were assessed for the 2.5 MV prototype imaging system. For image quality and imaging dose, a series of megavoltage cone‐beam scans were acquired for the head, thorax, and pelvis of an anthropomorphic phantom and were compared to kilovoltage cone‐beam and 6X megavoltage cone‐beam images. To demonstrate the advantage of MV imaging, a phantom with metallic inserts was scanned and the image quality was compared to CT and kilovoltage cone‐beam scans. With a lower energy beam and higher detector efficiency, the 2.5 MV imaging system generally yields better image quality than does the 6 MV imaging system with the conventional MV imager. In particular, with the anthropomorphic phantom studies, the contrast to noise of bone to tissue is generally improved in the 2.5 MV images compared to 6 MV. With an image quality sufficient for bony alignment, the imaging dose for 2.5 MV cone‐beam images is 2.4 − 3.4 MU compared to 26 MU in 6 MV cone‐beam scans for the head, thorax, and pelvis regions of the phantom. Unlike kilovoltage cone‐beam, the 2.5 MV imaging system does not suffer from high‐Z image artifacts. This can be very useful for treatment planning in cases where high‐Z prostheses are present. PACS number(s): 87.57.Q‐